2004
DOI: 10.1097/00002826-200401000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum Toxin in a Case of Hemimasticatory Spasm With Severe Worsening During Pregnancy

Abstract: Hemimasticatory spasm (HMS) is a rather uncommon movement disorder with a pathophysiology that is still unclear, although temporomasseter entrapment at the temporal fossa has been advanced. The authors present a case of HMS in a woman who experienced marked worsening in episode frequency and severity during pregnancy. Treatment with botulinum toxin led to marked improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…These authors concluded that, though the masticatory nucleus receives bilateral innervation, the contralateral hemisphere should exert [2,4,10,13,14,17] . This is supported by the presence of delayed jaw jerk [6,10,14,16] and the absence of silent periods of the masseter inhibitory reflexes [9,12,13,14,17,26] or 'efferent block' [26] . In patients with trigeminal neuropathy, both SP1 and SP2 components of the masseter inhibitory reflexes should be delayed or reduced in size, while a lesion to the masticatory nucleus or motor axons can cause an ipsilateral muscle weakness and a reduction in the voluntary EMG activity, but the reflex inhibition should remain evident [27] .…”
Section: Discussionmentioning
confidence: 92%
“…These authors concluded that, though the masticatory nucleus receives bilateral innervation, the contralateral hemisphere should exert [2,4,10,13,14,17] . This is supported by the presence of delayed jaw jerk [6,10,14,16] and the absence of silent periods of the masseter inhibitory reflexes [9,12,13,14,17,26] or 'efferent block' [26] . In patients with trigeminal neuropathy, both SP1 and SP2 components of the masseter inhibitory reflexes should be delayed or reduced in size, while a lesion to the masticatory nucleus or motor axons can cause an ipsilateral muscle weakness and a reduction in the voluntary EMG activity, but the reflex inhibition should remain evident [27] .…”
Section: Discussionmentioning
confidence: 92%
“…[3] Studies by Erdal J. (1996) [27] and Cersosimo MG. (2004) [28] have noticed that Botulinum Toxin A injection into the masticatory musculature diminishes the effects of hyperfunctional or spastic muscles.…”
Section: Oromandibular Dystonia: This Disease Ismentioning
confidence: 99%
“…Intramuscular Botox injections have resulted in relaxation of muscles, reducing inflammation of muscles and TMJ and the guarding response to pain thereby improving mouth opening. Several case reports have been published [73][74][75][76] describing the effectiveness of BTX-A in patients with hemimasticatory spasm, where all the patients responded positively to intramuscular Botox injections.…”
Section: Mandibular Spasmmentioning
confidence: 99%